2009
DOI: 10.1038/ki.2008.507
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone suppresses inflammation and prevents L-NAME–induced renal injury in rats

Abstract: Chronic inhibition of nitric oxide synthase by N(omega)-nitro- L-arginine methyl ester (L-NAME) causes progressive renal injury with systemic hypertension and interstitial macrophage infiltration. We have previously shown that there is local activation of the renin-angiotensin-aldosterone system in the renal cortex as a major pathogenic feature of macrophage infiltration. In this study, we measured the effects of the aldosterone antagonist, spironolactone, on renal injury in L-NAME-treated male Wistar rats. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 48 publications
(63 reference statements)
0
44
0
Order By: Relevance
“…Mice with the micro pumps exhibited serum concentrations of Aldo some four-to sixfold higher than observed in adrenally intact control mice. These Aldo concentrations, while not entirely physiologic, have been observed and even exceeded in adrenally intact but stimulated animals (24). In other animal models, even more modest interventions like daily diuretic administration have been shown to increase Aldo levels between two and three times those observed in controls (30,37).…”
Section: Discussionmentioning
confidence: 99%
“…Mice with the micro pumps exhibited serum concentrations of Aldo some four-to sixfold higher than observed in adrenally intact control mice. These Aldo concentrations, while not entirely physiologic, have been observed and even exceeded in adrenally intact but stimulated animals (24). In other animal models, even more modest interventions like daily diuretic administration have been shown to increase Aldo levels between two and three times those observed in controls (30,37).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, significant suppression of renal injury in the absence of a blood pressure-lowering effect was detected at 0.3 mg/kg CS-3150, suggesting that the renal protective effect of CS-3150 could not be explained simply by its antihypertensive action. Accumulating evidence has shown that aldosterone/MR signaling directly contributes to the pathogenesis of renal damage such as tubulointerstitial fibrosis through collagen accumulation (Sun et al, 2006;Diah et al, 2008), increased expression of proinflammatory cytokines in the kidney (Blasi et al, 2003;Ikeda et al, 2009), and renal reactive oxygen species generation by an NADPH oxidase-dependent mechanism (Beswick et al, 2001;Nishiyama et al, 2004). In the current study, upregulation of mRNA for several markers related to fibrosis (TGF-b1 and Col1a1), inflammation (MCP-1 and IL-6), and oxidative stress (p47phox and p67phox) was observed in the kidney of DOCA rats, and CS-3150 treatment inhibited these changes.…”
Section: Discussionmentioning
confidence: 99%
“…OPN expression signifi cantly increased in the cortex and has been correlated with the number of infi ltrating macrophages. In this model, the aldosterone antagonist markedly suppressed OPN expression [11]. In a rat crescentic glomerulonephritis model where macrophages and T cells infi ltrate with OPN expression at sites of infl ammation, treatment with an anti-OPN neutralizing antibody significantly reduced OPN expression and glomerulonephritis [12].…”
Section: Macrophage and Macrophage-derived Cellsmentioning
confidence: 97%